Positive electrode material, preparation method and lithium ion battery
By controlling the concentration distribution of the element m in the grains of the positive pole material, the pressure stress is formed, and the problem of the lattice expansion of the existing positive pole material during the charging and discharge process is improved, and the magnification performance and cycle stability are improved.
Patent Information
- Application Number
- CN202411959508.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-26
- Publication Date
- 2025-01-28
- Estimated Expiration
- 2044-12-26
AI Technical Summary
The lattice expansion of the existing positive electrode materials during charging and discharging leads to poor rate performance and cycle stability, and the lattice expansion effect caused by the bulk-phase doping method aggravates the cracking problem of particles.
By controlling the concentration distribution of element m in the grains of the positive pole material, the concentration of the surface area is higher, the central area concentration is low, forming the pressure stress from the surface facing the center, and the lattice expansion in the charging and charging process.
Effectively improve the percentage of the positive material and long -term cycle performance, reduce the micro -crack inside the grain, and improve the overall performance of the battery.
Smart Images

Figure CN119381445A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of lithium ion battery materials, and in particular to a positive electrode material, as well as a preparation method thereof and a lithium ion battery comprising the positive electrode material. Background Art
[0002] In the prior art, the lithium ions of some positive electrode materials have a long diffusion path during the charge and discharge process, which results in poor rate performance and cycle stability. In order to improve the rate performance and cycle stability of positive electrode materials, the prior art generally improves them by bulk doping of the positive electrode materials.
[0003] However, when some elements are doped into the crystal lattice, it will cause lattice expansion. In addition, the positive electrode material will also cause lattice expansion during long-term cycling. The superposition of these two effects will make it easier for microcracks to form inside the positive electrode material particles, which will in turn cause the particles to crack and cause the performance of the lithium battery to deteriorate.
[0004] Therefore, how to improve the rate performance and cycle stability of positive electrode materials is still a technical problem that needs to be solved urgently. Summary of the invention
[0005] One of the purposes of the present invention is to provide a positive electrode material, and another purpose of the present invention is to provide a method for preparing the positive electrode material of the present invention. In addition, another purpose of the present invention is to provide a lithium ion battery comprising the positive electrode material.
[0006] To achieve the above objectives, the technical solutions adopted by the present invention are specifically as follows.
[0007] In a first aspect, the present invention provides a positive electrode material, the chemical formula of the positive electrode material is: Li a Ni b Co c N1 d M (1-b-c-d-e) N2 e O2, wherein: 0.95≤a≤1.2, 0<b≤1, 0<c≤1, 0<d≤1, 0≤e<1, and b+c+d+e<1; the element M is selected from at least one element of Group IA and Group IA in the periodic table; the element N1 is selected from at least one of Mn and Al, and the element N2 is selected from at least one of Zr, Ti, Al, Co, Mg, W, Ce, and Y; The positive electrode material includes a plurality of crystal grains, and a cross section of the crystal grains includes a central region and a surface region. The cross section of the crystal grains is tested by EDS, and the average concentration of the element M in the central region is measured to be X1, and the average concentration of the element M in the surface region is X2, and X1 and X2 satisfy: 1.2≤X2 / X1≤20.
[0008] In a second aspect, the present invention provides a method for preparing a positive electrode material, comprising the steps of: S1: Mixing a salt solution containing Ni, Co and N1 with a salt solution containing element M to prepare a precursor solution; wherein the element N1 is selected from at least one of Mn and Al; S2: The precursor solution is subjected to spray pyrolysis treatment to prepare an oxide precursor, wherein the spray pyrolysis treatment includes spray treatment and annealing treatment, and the atomizing air flow rate of the spray treatment is 100m 3 / h~300m 3 / h, the atomization pressure is 400Kpa~700Kpa, the pyrolysis temperature is 400℃~1000℃, and the annealing temperature is 500℃~1200℃; S3: Mix the oxide precursor with a lithium source and a metal oxide containing element N2 and sinter them to obtain a positive electrode material; the element N2 is selected from at least one of Zr, Ti, Al, Co, Mg, W, Ce, and Y.
[0009] In a third aspect, the present invention further provides a lithium-ion battery, wherein the lithium-ion battery comprises the positive electrode material described in the present invention or the positive electrode material obtained by the preparation method described in the present invention.
[0010] The positive electrode material provided by the present invention is selected from the elements in the IA group and the IIA group in the periodic table, so that the concentration of the element M in the grain is controlled to satisfy 1.2≤X2 / X1≤20, so that the content of the element M near the surface area of the grain is relatively high, and the M element increases the unit cell volume of the surface area of the grain, while the content of the element M near the center area of the grain is relatively low, so that the unit cell volume in the center area of the grain is relatively small, thereby forming a compressive stress from the surface to the center of the grain, and the compressive stress can inhibit the lattice expansion during the charge and discharge process, thereby improving the gas production performance and long-term cycle performance.
[0011] The preparation method of the positive electrode material provided by the present invention performs doping of the target element at the precursor end, that is, firstly, the element M and the ternary nitrate solution containing Ni, Co and N1 are formed into a precursor solution, and then spray pyrolysis is performed to prepare an oxide precursor, and then during the spray pyrolysis process, the atomizing air flow rate, atomizing pressure and annealing temperature and other conditions are controlled to regulate the enrichment of the element M in the surface area of the oxide precursor, so that the concentration of the M element in the central area of the precursor is less than that in the surface area, thereby making the concentration of the M element in the surface area of the positive electrode material grains greater than that in the central area. BRIEF DESCRIPTION OF THE DRAWINGS
[0012] Figure 1 It is a schematic diagram of the test of the concentration distribution of the element M in the grains of the positive electrode material of the present invention; Figure 2 It is a comparison diagram of the concentration distribution of K element on the cross-section of multiple particles obtained by line scanning of the positive electrode materials provided in Example 1, Example 6, Example 7 and Comparative Example 2 of the present invention respectively; Figure 3 It is a comparison diagram of the concentration distribution of Mg element in the cross section of multiple particles obtained by line scanning of the positive electrode materials provided in Example 2, Example 6, Example 10 and Comparative Example 2 of the present invention respectively; Figure 4 It is a comparison diagram of internal cracks of the positive electrode materials provided by Example 6 of the present invention and Comparative Example 2; Figure 5 is a schematic diagram of a lithium-ion battery provided by the present invention in a discharge state; Figure 6 It is an explanatory diagram of the scanned area during the test of the average concentration X1 of the element M in the central area and the average concentration X2 in the surface area in the positive electrode material grains of the present invention. DETAILED DESCRIPTION
[0013] The technical solution of the present invention will be clearly and completely described below through embodiments. Obviously, the described embodiments are part of the embodiments of the present invention, rather than all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative work are within the scope of protection of the present invention.
[0014] It should be understood that the terms "first", "second", "third" and "fourth" etc. in the claims, specifications and drawings of the present invention are used to distinguish different objects rather than to describe a specific order. The terms "include" and "comprise" used in the specification and claims of the present invention indicate the presence of the described features, wholes, steps, operations, elements and / or components, but do not exclude the presence or addition of one or more other features, wholes, steps, operations, elements, components and / or their collections.
[0015] It should also be understood that the terms used in this specification of the present invention are only for the purpose of describing specific embodiments and are not intended to limit the present invention. As used in the specification of the present invention and the claims, the singular forms of "a", "an" and "the" are intended to include the plural forms unless the context clearly indicates otherwise. It should also be further understood that the term "and / or" used in the specification of the present invention and the claims refers to any combination of one or more of the associated listed items and all possible combinations, and includes these combinations.
[0016] Unless otherwise specified, the materials, reagents and equipment used in the examples and comparative examples of the present application are obtained from conventional commercial channels.
[0017] In a first aspect, the present invention provides a positive electrode material, the chemical formula of which is: Li a Ni b Co c N1 d M (1-b-c-d-e) N2 e O2, wherein: 0.95≤a≤1.2, 0<b≤1, 0<c≤1, 0<d≤1, 0≤e<1, and b+c+d+e<1; the element M is selected from at least one element of Group IA and Group IA in the periodic table; the element N1 is selected from at least one of Mn and Al, and the element N2 is selected from at least one of Zr, Ti, Al, Co, Mg, W, Ce, and Y; The positive electrode material includes a plurality of crystal grains. The cross section of the crystal grains is tested by EDS. The cross section of the crystal grains includes a central region and a surface region. The average concentration of the element M in the central region is measured to be X1, and the average concentration of the element M in the surface region is X2. X1 and X2 satisfy: 1.2≤X2 / X1≤20.
[0018] Therefore, by selecting element M from elements in group IA and group IIA in the periodic table, the concentration of element M in the grain is controlled to satisfy 1.2≤X2 / X1≤20, so that the content of element M near the surface area of the grain is relatively high, and the M element increases the unit cell volume of the surface area of the grain, while the content of element M near the center area of the grain is relatively small, so that the unit cell volume in the center area of the grain is relatively small, thereby forming compressive stress from the surface to the center of the grain. The compressive stress can inhibit the lattice expansion during the charge and discharge process, thereby improving the gas production performance and long-term cycle performance.
[0019] It should be noted that after the M element enters the transition metal layer and occupies the site of the Ni / Co / N1 element, the M element will expand the transition metal layer spacing and thus increase the unit cell volume; when the M element is enriched close to the grain surface, the unit cell volume of the grain surface region will be larger than the unit cell volume of the grain center region, and the stress in the surface region of the grain is larger, thereby generating compressive stress toward the center of the grain, thereby causing the grain to have a tendency to shrink from the surface to the center of the grain (i.e., a shrinkage state).
[0020] It should be noted that if Figure 1 As shown, in the cross-sectional view of the grain, the radius of the grain is L, the area from the center of the grain to the distance L / 2 from the center of the grain is the central area, and the area from the position L / 2 of the grain to the surface of the grain is the surface area.
[0021] In some preferred embodiments, the element M is selected from at least one element in the IA group and the IA group of the periodic table, for example, at least one element selected from Na, K, Mg, Ca, Sr, Ba, Sr, Rb, and Cs. These elements are monovalent, and the valence state is fixed after oxidation, which plays a role in stabilizing the crystal structure of the positive electrode material. In addition, the ionic radius of the above elements is relatively large. After entering the transition metal layer and occupying the site of the Ni / Co / N1 element, the M element with a large ionic radius will expand the distance between the transition metal layers, thereby increasing the unit cell volume.
[0022] In some preferred embodiments, the element N1 is selected from at least one of Mn and Al. The element N1 selected from Mn or Al can stabilize the crystal structure of the positive electrode material.
[0023] In some preferred embodiments, the element N2 is selected from at least one of Zr, Ti, Al, Co, Mg, W, Ce, and Y. The element N2 is selected from the above elements to stabilize the crystal structure of the positive electrode material and improve the ion conductivity. In addition, the element N2 can also delay the reaction between the positive electrode material and the electrolyte by coating the surface of the particles.
[0024] As an embodiment of the present invention, the value of X2 / X1 can be 1.2, 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, 13, 14, 15, 16, 17, 18, 19, 20 or any value between 1.2 and 20.
[0025] As an embodiment of the present invention, the X1 is 10ppm ~ 400ppm. Specifically, X1 can be 10ppm, 20ppm, 50ppm, 80ppm, 100ppm, 120ppm, 150ppm, 180ppm, 200ppm, 250ppm, 280ppm, 300ppm, 320ppm, 350ppm or 400ppm, etc., and of course, it can also be other values within the above range, which is not limited here. The value range of X1 is within the range, while stabilizing the crystal structure, it will not affect the capacity of the positive electrode material; if the content is high, it will occupy more transition metal or lithium ion sites, thereby affecting the normal charge and discharge performance.
[0026] As an embodiment of the present invention, the X2 is 10ppm ~ 400ppm. Specifically, X2 can be 10ppm, 20ppm, 50ppm, 80ppm, 100ppm, 120ppm, 150ppm, 180ppm, 200ppm, 250ppm, 280ppm, 300ppm, 320ppm, 350ppm or 400ppm, etc., and of course, it can also be other values within the above range, which is not limited here. The value range of X2 is within the range, while stabilizing the crystal structure, it will not affect the capacity of the positive electrode material; if the content is high, it will occupy more transition metal or lithium ion sites, thereby affecting the normal charge and discharge performance.
[0027] As an embodiment of the present invention, the content of element M in the positive electrode material is 10ppm~400ppm. Specifically, the content of element M in the positive electrode material can be 10ppm, 20ppm, 50ppm, 80ppm, 100ppm, 120ppm, 150ppm, 180ppm, 200ppm, 250ppm, 280ppm, 300ppm, 320ppm, 350ppm or 400ppm, etc., and of course it can also be other values within the above range, which are not limited here. When the content of element M is too low, the effect of doping cannot be achieved. When the content of element M is too high, the crystal grains contain too much M elements, which will cause the unit cell volume to change greatly, reduce its structural stability, and be detrimental to the long-term electrochemical performance of the battery. When the content of element M is controlled in the range of 10ppm~400ppm, fewer cracks can be produced during long-term cycling, and the cycle stability is better.
[0028] As an embodiment of the present invention, the content of element N2 in the positive electrode material is 0ppm~5000ppm. Specifically, the content of element N2 in the positive electrode material can be 0ppm, 5ppm, 100ppm, 500ppm, 1000ppm, 1500ppm, 1800ppm, 2000ppm, 2400ppm, 2800ppm, 3000ppm, 3500ppm, 4000ppm, 4500ppm, 4800ppm or 5000ppm, etc., and of course, it can also be other values within the above range, which is not limited here. When the concentration of element N2 is within the above range, the crystal structure can be stabilized, the ionic conductivity can be improved, and the reaction between the positive electrode material and the electrolyte can be delayed.
[0029] As an embodiment of the present invention, the lattice strain ε of the positive electrode material is less than 0.1%. Specifically, the lattice strain ε of the positive electrode material can be 0.095%, 0.09%, 0.05%, 0.01%, 0.005%, 0%, -0.01%, -0.05%, -0.08%, -0.10% or -0.15%, etc., and of course, it can also be other values within the above range, which are not limited here. By controlling the lattice strain ε within 0.1%, the microcracks inside the particles can be reduced, so that the particles of the positive electrode material are not easy to crack and fail during the cycle.
[0030] As an embodiment of the present invention, the specific surface area S of the positive electrode material is 0.4 m 2 / g~0.9m 2 / g. Specifically, the specific surface area S of the positive electrode material can be 0.4 m 2 / g, 0.45 m 2 / g, 0.50 m 2 / g, 0.55 m 2 / g, 0.58 m 2 / g, 0.60 m 2 / g, 0.70 m 2 / g, 0.75 m 2 / g, 0.80 m 2 / g, 0.85 m 2 / g or 0.9 m 2 / g, etc., and of course, it can also be other values within the above range, which is not limited here. Studies have found that the specific surface area S of the positive electrode material is greater than 0.9 m 2 / g, there are more particle powders, which are easy to react with the electrolyte during the charge and discharge process, resulting in gas production; and when the specific surface area S of the positive electrode material is less than 0.4 m 2 / g, the particle size is larger. The larger particle size leads to a too long lithium ion transmission channel and a relatively large internal resistance, which affects the kinetic process and the rate performance of the positive electrode material.
[0031] As an embodiment of the present invention, the tap density of the positive electrode material is ρ1>2.0 g / cm 3 ;The compaction density of the positive electrode material ρ2≥2.8 g / cm 3 Specifically, the tap density ρ1 of the positive electrode material can be 2.10 g / cm 3 , 2.12g / cm 3 , 2.18g / cm 3 , 2.20g / cm 3 , 2.22g / cm 3 , 2.24g / cm 3 , 2.30g / cm3 , 2.32g / cm 3 , 2.35g / cm 3 or 2.40g / cm 3 The compacted density ρ2 of the positive electrode material can be 2.80 g / cm 3 , 2.90g / cm 3 、3.00g / cm 3 、3.10g / cm 3 、3.15g / cm 3 、3.18g / cm 3 、3.20g / cm 3 、3.22g / cm 3 , 3.25g / cm 3 or 3.30g / cm 3 Of course, it can be other values within the above range, which is not limited here. The positive electrode material with higher tap density and compaction density has higher compaction density in the process of making the electrode sheet, and can exert higher capacity.
[0032] As an embodiment of the present invention, the volume particle size distribution width Span value of the positive electrode material satisfies: 1.5 ≥ Span value ≥ 1.0. Specifically, the Span value can be 1.0, 1.15, 1.18, 1.19, 1.20, 1.22, 1.24, 1.30, 1.35, 1.40, 1.45 or 1.50, etc., and of course it can also be other values within the above range, which is not limited here. The volume particle size distribution of the positive electrode material satisfies the above range, which can make the positive electrode material particles have a wider volume distribution as a whole, and it is easy to obtain a higher pole piece compaction, thereby improving the battery capacity.
[0033] As an embodiment of the present invention, the positive electrode material is a single crystal material, and the positive electrode material includes at least one grain with the same orientation, and the average particle size of the grain is 1µm~5µm. The positive electrode material contains single grains with the same orientation, wherein the average particle size of the single grain is 1µm~5µm. Specifically, the average particle size of a single grain is 1µm, 2um, 3um, 4um, 5µm, or any value within the range of any two of the above values, which is not limited here. The orientation of the primary particles of the positive electrode material is the same, and the average particle size of the primary particles is 1μm-5μm. Specifically, the average particle size of the primary particles is 1µm, 2um, 3um, 4um, 5µm, or any value within the range of any two of the above values, which is not limited here. The positive electrode material particles of the present application have single grains with the same orientation. Since single crystals have a more stable structure, more uniform distribution of bulk components, and better particle strength than polycrystalline, the material can greatly reduce the cracking of particles during the pressing process of the pole piece, and improve the compaction density and volume energy density of the pole piece.
[0034] It should be noted that the difference between single crystal positive electrode materials and polycrystalline positive electrode materials (i.e., polycrystalline secondary particles) is that the smallest particle of polycrystalline secondary particles is a secondary particle formed by the agglomeration of nanometer-scale primary particles. For single crystal positive electrode materials, the smallest particle is usually a single primary particle of micrometer scale. Generally speaking, in addition to EBSD testing methods, characterization methods such as scanning electron microscopy (SEM) can also be used to determine whether the obtained positive electrode product is a single crystal material. For example, for single crystal positive electrode materials, the morphology of single crystal particles can be characterized by SEM, and it can be seen that the shape of single crystal particles is generally regular or irregular spherical, and there is no significant particle agglomeration. The orientation of single crystal positive electrode materials can also be characterized by EBSD. Through EBSD, it can be observed that the color in at least one grain is the same, so as to judge that the orientation in at least one grain is the same, and the grains with the same orientation are single crystals. It should be specifically noted that the "single crystal positive electrode material" known to those skilled in the art is not a "single crystal" in the strict crystallographic sense. In crystallography, an ideal single crystal refers to a crystal with completely the same arrangement and orientation. However, due to impurities, strains and crystal defects, ideal single crystals are very rare and difficult to produce in the laboratory. Therefore, the single crystal cathode materials known in the art are actually more "single crystal morphology" cathode materials, which only show the size of large single crystal particles and are different from polycrystalline particles composed of many small primary particles.
[0035] As an embodiment of the present invention, the crystal grains include a substrate and a coating, and the coating is at least partially coated on the surface of the substrate. The coating is selected from at least one of ZrO2, TiO2, Al2O3, CoO, MgO, WO3, CeO2, and Y2O3. The coating can improve the chemical stability of the substrate material surface and improve the electrochemical performance of the positive electrode material.
[0036] It should be noted that, the positive electrode material provided by the present invention has two conditions for its crystal grains: in one condition, the crystal grains are a matrix, and there is no coating on the matrix; in another condition, the crystal grains include a matrix and a coating coated on the matrix.
[0037] In a second aspect, the present invention provides a method for preparing the positive electrode material of the present invention, comprising the steps of: S1: Mixing a salt solution containing Ni, Co and N1 with a salt solution containing element M to prepare a precursor solution; wherein the element N1 is selected from at least one of Mn and Al; S2: The precursor solution is subjected to spray pyrolysis treatment to prepare an oxide precursor, wherein the spray pyrolysis treatment includes spray treatment and annealing treatment, and the atomizing air flow rate of the spray treatment is 100m 3 / h~300m 3 / h, the atomization pressure is 400Kpa~700Kpa, the pyrolysis temperature is 400℃~1000℃, and the annealing temperature is 500℃~1200℃; S3: Mix the oxide precursor with a lithium source and a metal oxide containing element N2 and sinter them to obtain a positive electrode material; the element N2 is selected from at least one of Zr, Ti, Al, Co, Mg, W, Ce, and Y.
[0038] The method for preparing the positive electrode material provided by the present invention can use recycled positive electrode materials, or use pure metal salts of Ni, Co, and Ni as raw materials for preparation.
[0039] If recycled ternary cathode materials are used, the components of the recycled ternary cathode materials need to be tested first. This process is to confirm the content ratio of the main elements in the recycled materials and the types and ratios of the impurity elements present. Then, the cathode materials with confirmed components are mixed with pure metal salts of Ni / Co / N1 according to the final target Ni:Co:N1 molar ratio to form a nitrate solution.
[0040] As an embodiment of the present invention, in step S1, the molar ratio of Ni, Co, and N1 in the salt solution containing Ni, Co, and N1 is (55-70): (10-12): (20-33). Specifically, the molar ratio of Ni, Co, and N1 in the nitrate solution containing Ni, Co, and N1 can be 55:12:33, 70:12:33, 55:10:20, 70:10:20, 60:10:30, 65:12:33, 55:11:30, 70:11:30, 60:12:33 or 68:11:28, etc., and of course it can also be other values within the above range, which is not limited here.
[0041] As an embodiment of the present invention, in step S1, the N1 element may be Mn and / or Al.
[0042] A salt solution of element M is added to a nitrate solution in a target ratio to prepare a precursor solution; if the recovered ternary cathode material contains the target element M, the concentration of the element M to be added can be adjusted to ensure that the final concentration is the target concentration.
[0043] As an embodiment of the present invention, in step S1, the mass percentage concentration of the M element in the precursor solution is 0.01% to 0.06%. Specifically, the mass percentage concentration of the M element in the precursor solution can be 0.01%, 0.02%, 0.03%, 0.04%, 0.05% or 0.06%, etc., and of course it can also be other values within the above range, which are not limited here. By controlling the mass percentage concentration of the M element in the precursor solution within the range, the content of the element M in the prepared positive electrode material can be made to meet the range of 10ppm to 400ppm.
[0044] As an embodiment of the present invention, in step S1, the salt of element M includes at least one of chloride, sulfate, sulfite, nitrate, carbonate, and phosphate of element M. Element M is selected from at least one element in Group IA and Group IIA of the periodic table. For example, element M may be at least one of Na, K, Mg, Ca, Sr, Ba, Sr, Rb, and Cs.
[0045] As an embodiment of the present invention, the total concentration of Ni, Co, Ni, and M in the precursor solution is 2mol / L ~ 8mol / L. Specifically, the total concentration of Ni, Co, Ni, and M in the precursor solution can be 2.0mol / L, 2.5mol / L, 2.8mol / L, 3.0mol / L, 4.0mol / L, 4.5mol / L, 5.0mol / L, 5.5mol / L, 6.0mol / L, 6.4mol / L, 6.8mol / L, 7.0mol / L or 8.0mol / L, and of course it can be other values within the above range, which are not limited here. The total concentration of Ni, Co, Ni, and M in the precursor solution is within the above range, and the solid content of the spray droplets formed is moderate, and the solid phase as a nucleation site is conducive to the rapid solidification and nucleation of the droplets.
[0046] As an embodiment of the present invention, the spray pyrolysis includes spray treatment and annealing treatment. The atomizing air flow rate of the spray treatment is 100m 3 / h~300m 3 / h, the atomization pressure is 400Kpa~700Kpa, and the pyrolysis temperature is 400℃~1000℃. Specifically, the atomization air flow rate of the spray treatment can be 100m 3 / h、120m 3 / h、150m 3 / h、180m 3 / h、200m 3 / h、240m 3 / h、280m 3 / h or 300m 3 / h, of course, it can also be other values within the above range, which is not limited here. The atomization pressure can be 400Kpa, 420Kpa, 450Kpa, 500Kpa, 540Kpa, 580Kpa, 600Kpa, 650Kpa or 700Kpa, of course, it can also be other values within the above range, which is not limited here. The pyrolysis temperature can be 400℃, 450℃, 500℃, 600℃, 650℃, 700℃, 800℃, 900℃ or 1000℃, of course, it can also be other values within the above range, which is not limited here. The atomization air flow rate, atomization pressure and pyrolysis temperature of the spray treatment are controlled within the above range. By adjusting the appropriate atomization air flow rate, atomization pressure and pyrolysis temperature, the time for the precursor solution to form dehydrated particles can be controlled, which promotes the enrichment of M element in the surface area of the dehydrated particles.
[0047] As an embodiment of the present invention, the temperature of the annealing treatment is 500°C to 1200°C. Specifically, the temperature of the annealing treatment can be 500°C, 600°C, 650°C, 700°C, 800°C, 850°C, 900°C, 960°C, 1000°C, 1050°C, 1100°C, 1140°C or 1200°C, and of course, it can also be other values within the above range, which are not limited here. A higher annealing temperature can make the dehydrated particles form oxide precursors.
[0048] The method for preparing the positive electrode material of the present invention provided by the present invention can effectively regulate the internal and external distribution difference of the element M by controlling the spray treatment and annealing treatment during the spray pyrolysis process, so that the concentration X1 of the element M in the central area and the concentration X2 in the surface area of the prepared positive electrode material grains satisfy: 1.2≤X2 / X1≤20.
[0049] As an embodiment of the present invention, in step S3, the oxide precursor is first crushed to a D50 of 2.0 μm to 4.0 μm, and then used for mixing. Specifically, the oxide precursor can be crushed to a D50 of 2.0 μm, 2.2 μm, 2.5 μm, 3.0 μm, 3.5 μm, 3.8 μm or 4.0 μm, and of course it can be other values within the above range, which are not limited here. The oxide precursor is crushed to a D50 of 2.0 μm to 4.0 μm before being used for mixing. The positive electrode material powder obtained from the precursor at this particle size is less and the grains are more rounded.
[0050] As an embodiment of the present invention, in step S3, the lithium source can be selected from any one or more of lithium carbonate, lithium nitrate, and lithium hydroxide.
[0051] As an embodiment of the present invention, in step S3, the metal oxide containing element N2 is selected from any one or more of ZrO2, TiO2, Al2O3, CoO, MgO, WO3, CeO2, and Y2O3; preferably, the metal oxide containing element N2 is CeO2 and / or WO3, and further preferably, the metal oxide containing element N2 is CeO2.
[0052] As an embodiment of the present invention, in step S3, the oxide precursor, the lithium source, and the metal oxide containing the element N2 are mixed in a mass ratio of 1: (0.4-0.8): (0.003-0.006). Specifically, the oxide precursor, the lithium source, and the metal oxide containing the element N2 are mixed in a mass ratio of 1: 0.4: 0.003, 1: 0.5: 0.004, 1: 0.6: 0.006, 1: 0.5: 0.003, 1: 0.5: 0.005, 1: 0.8: 0.003, 1: 0.8: 0.006, 1: 0.4: 0.006 or 1: 0.5: 0.004. Of course, it can also be other values within the above range, which are not limited here. By limiting the mass ratio of several reaction materials of the oxide precursor, the lithium source, and the metal oxide containing the element N2, a positive electrode material having the chemical formula of the present invention can be obtained.
[0053] As an embodiment of the present invention, in step S3, the heating rate of the heating section of sintering is controlled to be 0.5℃ / min~3℃ / min, and the holding time of sintering is 8h~16h. Specifically, the heating rate of the heating section of sintering can be controlled to be 0.5℃ / min, 1.0℃ / min, 1.2℃ / min, 1.5℃ / min, 1.8℃ / min, 2.0℃ / min, 2.5℃ / min or 3.0℃ / min. Of course, it can also be other values within the above range, which is not limited here. The heating rate of the heating section is controlled within the above range, and the slow heating can make the lithium insertion more sufficient and the grain nucleation more sufficient. Specifically, the holding time of sintering can be 8h, 8.5h, 9.0h, 10h, 10.5h, 11h, 12h, 13h, 14h, 15h or 16h. Of course, it can also be other values within the above range, which is not limited here. When the sintering holding time is within the above range, the grain growth is more sufficient, and there is less grain agglomeration in the obtained positive electrode material. As an embodiment of the present invention, the sintered material is subjected to airflow pulverization and then coated, and the volume distribution particle size median D50 of the pulverized sintered material is controlled to be 3.0μm~5.0μm. Specifically, the matrix can be pulverized to D50 of 3.0μm, 3.5μm, 3.8μm, 4.0μm, 4.5μm or 5.0μm, and of course it can be other values within the above range, which is not limited here. The particle size D50 of the matrix airflow pulverization is controlled to the above range, and this particle size range corresponds to the particle size range of the pulverized particle size D50 of the oxide precursor, ensuring a good pulverization effect.
[0054] As an embodiment of the present invention, the coating agent used in the coating treatment is selected from at least one of ZrO2, TiO2, Al2O3, CoO, MgO, WO3, CeO2, and Y2O3.
[0055] In a third aspect, the present invention further provides a lithium-ion battery, wherein the lithium-ion battery comprises the positive electrode material described in the present invention or the positive electrode material obtained by the preparation method described in the present invention.
[0056] As an embodiment of the present application, the present application provides a secondary battery, including a housing, an electrode assembly and an electrolyte / electrolyte. The electrode assembly and the electrolyte / electrolyte are both located in the housing. The housing may be a packaging bag encapsulated by a packaging film (such as an aluminum-plastic film), such as when the secondary battery is a soft-pack battery. In other embodiments, the secondary battery may also be a steel shell battery, an aluminum shell battery, etc.
[0057] Figure 5 A schematic diagram of a battery in a discharge state, i.e., during operation, is shown. As shown in the figure, the electrode assembly includes a positive electrode sheet 110, a negative electrode sheet 120, and a separator 130, and the separator is disposed between the positive electrode sheet and the negative electrode sheet. The electrode assembly can be a laminated structure, which is formed by alternately stacking the positive electrode sheet, the separator, and the negative electrode sheet in sequence. In other embodiments, the electrode assembly can also be a winding structure, which is formed by stacking the positive electrode sheet, the separator, and the negative electrode sheet in sequence and then winding them.
[0058] 〈Positive electrode〉 The positive electrode sheet 110 includes a positive electrode current collector 111 and a positive electrode active layer 112 disposed on at least one surface of the positive electrode current collector. The positive electrode current collector may be aluminum foil or nickel foil, or may be any composite current collector disclosed in the prior art, such as but not limited to the current collector formed by combining the aforementioned conductive foil and a polymer substrate. The positive electrode active layer contains a positive electrode active material, and the positive electrode active material includes the positive electrode material provided by the present invention or the positive electrode material obtained by the preparation method of the present invention.
[0059] Negative electrode The negative electrode sheet 120 includes a negative electrode current collector 121 and a negative electrode active material layer 122 disposed on at least one surface of the negative electrode current collector. The negative electrode current collector may be at least one of copper foil, nickel foil, stainless steel foil, titanium foil or carbon-based current collector, or may be any composite current collector disclosed in the prior art, such as but not limited to a current collector formed by combining the aforementioned conductive foil and a polymer substrate. The negative electrode active material layer includes a negative electrode material.
[0060] During battery operation, that is, when the battery is in a discharge state, the metal ions 140 (e.g., lithium ions) in the negative electrode are released from the lattice of the negative electrode material, pass through the separator 130 through the electrolyte / electrolyte, and are embedded in the lattice of the positive electrode material. Conversely, when the battery is charged by applying an external circuit, the oxidation of the positive electrode material causes the metal ions (e.g., lithium ions) in the positive electrode to be released from the lattice of the positive electrode material, pass through the separator through the electrolyte / electrolyte, and move to the negative electrode; at the same time, the negative electrode material undergoes a reduction reaction, causing the metal ions to be embedded in the lattice of the negative electrode material. As the metal ions go back and forth between the positive and negative electrodes, the battery can achieve the discharge and charge process in thousands of cycles.
[0061] In some embodiments, the silicon-based material in the negative electrode material may include at least one of amorphous silicon, crystalline silicon, silicon oxide, and silicate.
[0062] In some embodiments, the silicon-based material includes silicon oxide, the silicon oxide includes silicon element and oxygen element, and the atomic ratio of the silicon element to the oxygen element is 0~2, and does not include 0.
[0063] In some embodiments, the silicon-based material includes silicon oxide, and the chemical formula of silicon oxide is SiOx, where 0<x≤2. Specifically, SiOx can be SiO 0.5 、SiO 0.7 、SiO 0.9 、SiO、SiO 1.2 、SiO 1.5 、SiO 1.8 、SiO 1.9 etc., which are not limited here. Silicon oxide can be represented by the general formula SiOx (0<x≤2). It can be a material formed by silicon dispersed in SiO2; it can also be a material with a tetrahedral structural unit, in which the silicon atom is located at the center of the tetrahedral structural unit, and the oxygen atoms and / or silicon atoms are located at the four vertices of the tetrahedral structural unit.
[0064] In some embodiments, the graphite material in the negative electrode material may include at least one of natural graphite, artificial graphite, expanded graphite, and oxidized graphite.
[0065] In some embodiments, the negative electrode material includes a carbon material, and the carbon material includes at least one of amorphous carbon and graphitized carbon.
[0066] Specific Examples and Comparative Examples Example 1 This embodiment provides a positive electrode material, and the preparation process is as follows: (1) Take metal salts of Ni, Co, and Mn, prepare a nitrate solution according to the molar ratio of Ni:Co:Mn=55:12:33, add K chloride solution to the nitrate solution to prepare a precursor solution, the mass ratio content of K element in the precursor solution is 0.01%, and the total concentration of Ni, Co, Mn, and K in the precursor solution is 5 mol / L; (2) The precursor solution is sprayed and then annealed to prepare an oxide precursor, wherein the atomizing air flow rate of the spraying treatment is 200m 3 / h, atomization pressure is 550Kpa, pyrolysis temperature is 500℃, and annealing temperature is 1000℃; (3) The oxide precursor is crushed, and the volume distribution particle size median D50 of the crushed oxide precursor is 3.24 μm; 400 g of the crushed oxide precursor is uniformly mixed with 186.72 g of lithium carbonate and 1.8 g of CeO2, and sintered at 960°C in a compressed air atmosphere, the heating rate of the heating stage of the sintering is controlled to be 2°C / min, and the sintering holding time is 8 hours to obtain a sintered product; (4) The sintered material is crushed to obtain a crushed material, and the median volume distribution particle size D50 of the crushed material is 4.2 μm; 300 g of the crushed material is mixed with 0.5 g of WO3, and the mixture is sintered at 550°C for 8 h in an oxygen atmosphere to obtain a sintered material. The sintered material is sieved and demagnetized to obtain a positive electrode material.
[0067] Example 2 This embodiment provides a positive electrode material, and the preparation process is as follows: (1) Take metal salts of Ni, Co, and Mn and prepare a nitrate solution in a molar ratio of Ni:Co:Mn=60:10:30, add a Mg sulfate solution to the nitrate solution to prepare a precursor solution, the mass ratio content of Mg element in the precursor solution is 0.01%, and the total concentration of Ni, Co, Mn, and Mg in the precursor solution is 5 mol / L; (2) Spray pyrolysis includes spraying the precursor solution and then annealing it to produce an oxide precursor, wherein the atomizing air flow rate of the spray treatment is 220m 3 / h, atomization pressure is 500Kpa, pyrolysis temperature is 600℃, and annealing temperature is 900℃; (3) The oxide precursor is crushed, and the volume distribution particle size median D50 of the crushed oxide precursor is 3.16 μm; 400 g of the crushed oxide precursor is uniformly mixed with 186.72 g of lithium carbonate and 1.8 g of CeO2, and sintered at 950°C in an oxygen atmosphere, with the heating rate of the heating stage of the sintering being controlled at 3°C / min, and the sintering holding time being 8 h to obtain a sintered product; (4) The sintered material is crushed to obtain a crushed material, and the median volume distribution particle size D50 of the crushed material is 4.5 μm; 300 g of the crushed material is mixed with 0.5 g of WO3, and the mixture is sintered at 550°C for 8 h in an oxygen atmosphere to obtain a sintered material. The sintered material is sieved and demagnetized to obtain a positive electrode material.
[0068] Example 3 This embodiment provides a positive electrode material, and the preparation process is as follows: (1) Take metal salts of Ni, Co, and Mn, prepare a nitrate solution according to the molar ratio of Ni:Co:Mn=55:12:33, add Ca chloride solution to the nitrate solution to prepare a precursor solution, the mass ratio content of Ca element in the precursor solution is 0.01%, and the total concentration of Ni, Co, Mn, and Ca in the precursor solution is 5 mol / L; (2) Spray pyrolysis includes spraying the precursor solution and then annealing it to produce an oxide precursor, wherein the atomizing air flow rate of the spray treatment is 180m 3 / h, atomization pressure is 600Kpa, pyrolysis temperature is 800℃, and annealing temperature is 1100℃; (3) The oxide precursor is crushed, and the volume distribution particle size median D50 of the crushed oxide precursor is 3.36 μm; 400 g of the crushed oxide precursor is uniformly mixed with 186.72 g of lithium carbonate and 1.8 g of CeO2, and sintered at 960°C in a compressed air atmosphere, the heating rate of the heating stage of the sintering is controlled to be 1°C / min, and the sintering holding time is 8 hours to obtain a sintered product; (4) The sintered material is crushed to obtain a crushed material, wherein the volume distribution median particle size D50 of the sintered material is 4.8 μm; 300 g of the crushed material is mixed with 0.5 g of WO3, and the mixture is sintered at 550°C for 8 h in an oxygen atmosphere to obtain a sintered material. The sintered material is sieved and demagnetized to obtain a positive electrode material.
[0069] Example 4 This embodiment provides a positive electrode material, and the preparation process is as follows: (1) Take metal salts of Ni, Co, and Mn and prepare a nitrate solution in a molar ratio of Ni:Co:Mn=55:12:33, add a chloride solution of Ba to the nitrate solution to prepare a precursor solution, the mass ratio content of Ba element in the precursor solution is 0.01%, and the total concentration of Ni, Co, Mn, and Ba in the precursor solution is 5 mol / L; (2) The precursor solution is sprayed and then annealed to prepare an oxide precursor, wherein the atomizing air flow rate of the spraying treatment is 200m 3 / h, atomization pressure is 500Kpa, pyrolysis temperature is 800℃, annealing temperature is 1000℃; (3) The oxide precursor is crushed, and the volume distribution particle size median D50 of the crushed oxide precursor is 3.05 μm; 400 g of the crushed oxide precursor is uniformly mixed with 186.72 g of lithium carbonate and 1.8 g of CeO2, and sintered at 960°C in a compressed air atmosphere, the heating rate of the heating stage of the sintering is controlled to be 1°C / min, and the sintering holding time is 8 hours to obtain a sintered product; (4) The sintered material is crushed to obtain a crushed material, and the median volume distribution particle size D50 of the crushed material is 3.5 μm; 300 g of the crushed material is mixed with 0.5 g of WO3, and the mixture is sintered at 550°C for 8 h in an oxygen atmosphere to obtain a sintered material. The sintered material is sieved and demagnetized to obtain a positive electrode material.
[0070] Example 5 This embodiment provides a positive electrode material, and the preparation process is as follows: (1) Take metal salts of Ni, Co, and Mn, prepare a nitrate solution according to the molar ratio of Ni:Co:Mn=55:12:33, add a nitrate solution of Sr to the nitrate solution to prepare a precursor solution, the mass ratio content of Sr element in the precursor solution is 0.01%, and the total concentration of Ni, Co, Mn, and Sr in the precursor solution is 5 mol / L; (2) The precursor solution is sprayed and then annealed to prepare an oxide precursor, wherein the atomizing air flow rate of the spraying process is 150m 3 / h, atomization pressure is 650Kpa, pyrolysis temperature is 700℃, annealing temperature is 800℃; (3) The oxide precursor is crushed, and the volume distribution particle size median D50 of the crushed oxide precursor is 3.50 μm; 400 g of the crushed oxide precursor is uniformly mixed with 186.72 g of lithium carbonate and 1.8 g of CeO2, and sintered at 960°C in a compressed air atmosphere, the heating rate of the heating stage of the sintering is controlled to be 2°C / min, and the sintering holding time is 8 hours to obtain a sintered product; (4) The sintered material is crushed to obtain a crushed material, and the median volume distribution particle size D50 of the crushed material is 4.2 μm; 300 g of the crushed material is mixed with 0.5 g of WO3, and the mixture is sintered at 550°C for 8 h in an oxygen atmosphere to obtain a sintered material. The sintered material is sieved and demagnetized to obtain a positive electrode material.
[0071] Example 6 This embodiment provides a positive electrode material, and the preparation process is as follows: (1) Take metal salts of Ni, Co, and Mn and prepare a nitrate solution in a molar ratio of Ni:Co:Mn=55:12:33, add a chloride solution of K and a chloride solution of Mg to the nitrate solution to prepare a precursor solution, wherein the mass ratio content of K element and Mg element in the precursor solution is 0.02% each, and the total concentration of Ni, Co, Mn, K, and Mg in the precursor solution is 5 mol / L; (2) The precursor solution is sprayed and then annealed to prepare an oxide precursor, wherein the atomizing air flow rate of the spraying treatment is 200m 3 / h, atomization pressure is 550Kpa, pyrolysis temperature is 900℃, annealing temperature is 1000℃; (3) The oxide precursor is crushed, and the volume distribution particle size median D50 of the crushed oxide precursor is 3.28 μm; 400 g of the crushed oxide precursor is uniformly mixed with 186.72 g of lithium carbonate and 1.8 g of CeO2, and sintered at 960°C in a compressed air atmosphere, the heating rate of the heating stage of the sintering is controlled to be 3°C / min, and the sintering holding time is 8 hours to obtain a sintered product; (4) The sintered material is crushed to obtain a crushed material, wherein the median volume distribution particle size D50 of the crushed material is 4.0 μm; 300 g of the crushed material is mixed with 0.5 g of WO3, and the mixture is sintered at 550°C for 8 h in an oxygen atmosphere to obtain a sintered material. The sintered material is sieved and demagnetized to obtain a positive electrode material.
[0072] Example 7 This embodiment provides a positive electrode material, and the preparation process is as follows: (1) Take metal salts of Ni, Co, and Mn and prepare a nitrate solution in a molar ratio of Ni:Co:Mn=55:12:33, add a sulfate solution of K and a nitrate solution of Ca to the nitrate solution to prepare a precursor solution, wherein the mass ratio content of K element and Ca element in the precursor solution is 0.02% each, and the total concentration of Ni, Co, Mn, K, and Ca in the precursor solution is 5 mol / L; (2) The precursor solution is sprayed and then annealed to prepare an oxide precursor, wherein the atomizing air flow rate of the spraying process is 240m 3 / h, atomization pressure is 450Kpa, pyrolysis temperature is 600℃, and annealing temperature is 950℃; (3) The oxide precursor is crushed, and the volume distribution particle size median D50 of the crushed oxide precursor is 2.96 μm; 400 g of the crushed oxide precursor is uniformly mixed with 186.72 g of lithium carbonate and 1.8 g of CeO2, and sintered at 960°C in a compressed air atmosphere, the heating rate of the heating stage of the sintering is controlled to be 2°C / min, and the sintering holding time is 8 hours to obtain a sintered product; (4) The sintered material is crushed to obtain a crushed material, and the median volume distribution particle size D50 of the crushed material is 4.7 μm; 300 g of the crushed material is mixed with 0.5 g of WO3, and the mixture is sintered at 550°C for 8 h in an oxygen atmosphere to obtain a sintered material. The sintered material is sieved and demagnetized to obtain a positive electrode material.
[0073] Example 8 This embodiment provides a positive electrode material, and the preparation process is as follows: (1) Take metal salts of Ni, Co, and Mn and prepare a nitrate solution in a molar ratio of Ni:Co:Mn=55:12:33, add a chloride solution of K and a chloride solution of Ba to the nitrate solution to prepare a precursor solution, wherein the mass ratio content of K element and Ba element in the precursor solution is 0.02% each, and the total concentration of Ni, Co, Mn, K, and Ba in the precursor solution is 5 mol / L; (2) The precursor solution is sprayed and then annealed to prepare an oxide precursor, wherein the atomizing air flow rate of the spraying treatment is 200m 3 / h, atomization pressure is 600Kpa, pyrolysis temperature is 700℃, and annealing temperature is 1000℃; (3) The oxide precursor is crushed, and the volume distribution particle size median D50 of the crushed oxide precursor is 3.10 μm; 400 g of the crushed oxide precursor is uniformly mixed with 186.72 g of lithium carbonate and 1.8 g of CeO2, and sintered at 960°C in a compressed air atmosphere, the heating rate of the heating stage of the sintering is controlled to be 1.5°C / min, and the sintering holding time is 8 hours to obtain a sintered product; (4) The sintered material is crushed to obtain a crushed material, and the median volume distribution particle size D50 of the crushed material is 3.7 μm; 300 g of the crushed material is mixed with 0.5 g of WO3, and the mixture is sintered at 550°C for 8 h in an oxygen atmosphere to obtain a sintered material. The sintered material is sieved and demagnetized to obtain a positive electrode material.
[0074] Example 9 This embodiment provides a positive electrode material, and the preparation process is as follows: (1) Take metal salts of Ni, Co, and Mn and prepare a nitrate solution in a molar ratio of Ni:Co:Mn=55:12:33, add a chloride solution of K and a chloride solution of Sr to the nitrate solution to prepare a precursor solution, wherein the mass ratio content of K element and Sr element in the precursor solution is 0.02% each, and the total concentration of Ni, Co, Mn, K, and Sr in the precursor solution is 5 mol / L; (2) The precursor solution is sprayed and then annealed to prepare an oxide precursor, wherein the atomizing air flow rate of the spraying process is 180m 3 / h, atomization pressure is 500Kpa, pyrolysis temperature is 650℃, and annealing temperature is 1000℃; (3) The oxide precursor is crushed, and the volume distribution particle size median D50 of the crushed oxide precursor is 3.25 μm; 400 g of the crushed oxide precursor is uniformly mixed with 186.72 g of lithium carbonate and 1.8 g of CeO2, and sintered at 960°C in a compressed air atmosphere, the heating rate of the heating stage of the sintering is controlled to be 0.5°C / min, and the sintering holding time is 8 hours to obtain a sintered product; (4) The sintered material is crushed to obtain a crushed material, and the median volume distribution particle size D50 of the crushed material is 4.3 μm; 300 g of the crushed material is mixed with 0.5 g of WO3, and the mixture is sintered at 550°C for 8 h in an oxygen atmosphere to obtain a sintered material. The sintered material is sieved and demagnetized to obtain a positive electrode material.
[0075] Example 10 This embodiment provides a positive electrode material, and the preparation process is as follows: (1) Take metal salts of Ni, Co and Mn and prepare a chloride solution in a molar ratio of Ni:Co:Mn=55:12:33, add a chloride solution of Mg and a chloride solution of Ca to the chloride solution to prepare a precursor solution, wherein the mass ratio content of Mg element and Ca element in the precursor solution is 0.03% each, and the total concentration of Ni, Co, Mn, Mg and Ca in the precursor solution is 5 mol / L; (2) The precursor solution is sprayed and then annealed to prepare an oxide precursor, wherein the atomizing air flow rate of the spraying treatment is 200m 3 / h, atomization pressure is 580Kpa, pyrolysis temperature is 700℃, and annealing temperature is 1000℃; (3) The oxide precursor is crushed, and the volume distribution particle size median D50 of the crushed oxide precursor is 3.75 μm; 400 g of the crushed oxide precursor is uniformly mixed with 186.72 g of lithium carbonate and 1.8 g of CeO2, and sintered at 960°C in a compressed air atmosphere, the heating rate of the heating stage of the sintering is controlled to be 1.5°C / min, and the sintering holding time is 8 hours to obtain a sintered product; (4) The sintered material is crushed to obtain a crushed material, and the median volume distribution particle size D50 of the crushed material is 4.8 μm; 300 g of the crushed material is mixed with 0.5 g of WO3, and the mixture is sintered at 550°C for 8 h in an oxygen atmosphere to obtain a sintered material. The sintered material is sieved and demagnetized to obtain a positive electrode material.
[0076] Embodiment 11 This embodiment provides a positive electrode material, and the preparation process is as follows: (1) Take metal salts of Ni, Co, and Mn and prepare a nitrate solution in a molar ratio of Ni:Co:Mn=55:12:33, and add a nitrate solution of Mg and a nitrate solution of Ba to the nitrate solution to prepare a precursor solution. The mass ratio content of Mg element and Ba element in the precursor solution is 0.03% each, and the total concentration of Ni, Co, Mn, Mg, and Ba in the precursor solution is 5 mol / L; (2) The precursor solution is sprayed and then annealed to prepare an oxide precursor, wherein the atomizing air flow rate of the spraying process is 150m 3 / h, atomization pressure is 550Kpa, pyrolysis temperature is 800℃, and annealing temperature is 1000℃; (3) The oxide precursor is crushed, and the volume distribution particle size median D50 of the crushed oxide precursor is 3.21 μm; 400 g of the crushed oxide precursor is uniformly mixed with 186.72 g of lithium carbonate and 1.8 g of CeO2, and sintered at 960°C in a compressed air atmosphere, the heating rate of the heating stage of the sintering is controlled to be 1°C / min, and the sintering holding time is 8 hours to obtain a sintered product; (4) The sintered material is crushed to obtain a crushed material, and the median volume distribution particle size D50 of the crushed material is 4.1 μm; 300 g of the crushed material is mixed with 0.5 g of WO3, and the mixture is sintered at 550°C for 8 h in an oxygen atmosphere to obtain a sintered material. The sintered material is sieved and demagnetized to obtain a positive electrode material.
[0077] Example 12 This embodiment provides a positive electrode material, and the preparation process is as follows: (1) Take metal salts of Ni, Co, and Mn and prepare a nitrate solution in a molar ratio of Ni:Co:Mn=55:12:33, and add a chloride solution of Mg and a chloride solution of Sr to the nitrate solution to prepare a precursor solution. The mass ratio content of Mg element and Sr element in the precursor solution is 0.03%, and the total concentration of Ni, Co, Mn, Mg, and Sr in the precursor solution is 5 mol / L; (2) The precursor solution is sprayed and then annealed to prepare an oxide precursor, wherein the atomizing air flow rate of the spraying process is 120m 3 / h, atomization pressure is 700Kpa, pyrolysis temperature is 900℃, and annealing temperature is 1000℃; (3) The oxide precursor is crushed, and the volume distribution particle size median D50 of the crushed oxide precursor is 3.19 μm; 400 g of the crushed oxide precursor is uniformly mixed with 186.72 g of lithium carbonate and 1.8 g of CeO2, and sintered at 960°C in a compressed air atmosphere, the heating rate of the heating stage of the sintering is controlled to be 3°C / min, and the sintering holding time is 8 hours to obtain a sintered product; (4) The sintered material is crushed to obtain a crushed material, and the median volume distribution particle size D50 of the crushed material is 4.2 μm; 300 g of the crushed material is mixed with 0.5 g of WO3, and the mixture is sintered at 550°C for 8 h in an oxygen atmosphere to obtain a sintered material. The sintered material is sieved and demagnetized to obtain a positive electrode material.
[0078] Embodiment 13 This embodiment provides a positive electrode material, and the preparation process is as follows: (1) Take metal salts of Ni, Co, and Mn and prepare a nitrate solution in a molar ratio of Ni:Co:Mn=55:12:33, and add a chloride solution of Ca and a chloride solution of Ba to the nitrate solution to prepare a precursor solution. The mass ratio of the Ca element and the Ba element in the precursor solution is 0.03%, and the total concentration of Ni, Co, Mn, Ca, and Ba in the precursor solution is 5 mol / L; (2) The precursor solution is sprayed and then annealed to prepare an oxide precursor, wherein the atomizing air flow rate of the spraying treatment is 200m 3 / h, atomization pressure is 600Kpa, pyrolysis temperature is 600℃, and annealing temperature is 1000℃; (3) The oxide precursor is crushed, and the volume distribution particle size median D50 of the crushed oxide precursor is 3.38 μm; 400 g of the crushed oxide precursor is uniformly mixed with 186.72 g of lithium carbonate and 1.8 g of CeO2, and sintered at 960°C in a compressed air atmosphere, the heating rate of the heating stage of the sintering is controlled to be 3°C / min, and the sintering holding time is 8 hours to obtain a sintered product; (4) The sintered material is crushed to obtain a crushed material, and the median volume distribution particle size D50 of the crushed material is 4.2 μm; 300 g of the crushed material is mixed with 0.5 g of WO3, and the mixture is sintered at 550°C for 8 h in an oxygen atmosphere to obtain a sintered material. The sintered material is sieved and demagnetized to obtain a positive electrode material.
[0079] Embodiment 14 This embodiment provides a positive electrode material, and the preparation process is as follows: (1) Take metal salts of Ni, Co, and Mn and prepare a nitrate solution in a molar ratio of Ni:Co:Mn=55:12:33, and add a nitrate solution of Ca and a nitrate solution of Sr to the nitrate solution to prepare a precursor solution. The mass ratio of the Ca element and the Sr element in the precursor solution is 0.03%, and the total concentration of Ni, Co, Mn, Ca, and Sr in the precursor solution is 5 mol / L; (2) The precursor solution is sprayed and then annealed to prepare an oxide precursor, wherein the atomizing air flow rate of the spraying treatment is 200m 3 / h, atomization pressure is 600Kpa, pyrolysis temperature is 1000℃, and annealing temperature is 1000℃; (3) The oxide precursor is crushed, and the volume distribution particle size median D50 of the crushed oxide precursor is 3.48 μm; 400 g of the crushed oxide precursor is uniformly mixed with 186.72 g of lithium carbonate and 1.8 g of CeO2, and sintered at 960°C in a compressed air atmosphere, the heating rate of the heating stage of the sintering is controlled to be 2°C / min, and the sintering holding time is 8 hours to obtain a sintered product; (4) The sintered material is crushed to obtain a crushed material, and the median volume distribution particle size D50 of the crushed material is 4.4 μm; 300 g of the crushed material is mixed with 0.5 g of WO3, and the mixture is sintered at 550°C for 8 h in an oxygen atmosphere to obtain a sintered material. The sintered material is sieved and demagnetized to obtain a positive electrode material.
[0080] Embodiment 15 This embodiment provides a positive electrode material, and the preparation process is as follows: (1) Take metal salts of Ni, Co, and Mn and prepare a nitrate solution in a molar ratio of Ni:Co:Mn=55:12:33, and add a chloride solution of Ba and a chloride solution of Sr to the nitrate solution to prepare a precursor solution. The mass ratio of Ba element and Sr element in the precursor solution is 0.03%, and the total concentration of Ni, Co, Mn, Ba, and Sr in the precursor solution is 5 mol / L; (2) The precursor solution is sprayed and then annealed to prepare an oxide precursor, wherein the atomizing air flow rate of the spraying treatment is 200m 3 / h, atomization pressure is 550Kpa, pyrolysis temperature is 600℃, annealing temperature is 1200℃; (3) The oxide precursor is crushed, and the volume distribution particle size median D50 of the crushed oxide precursor is 3.52 μm; 400 g of the crushed oxide precursor is uniformly mixed with 186.72 g of lithium carbonate and 1.8 g of CeO2, and sintered at 960°C in a compressed air atmosphere, the heating rate of the heating stage of the sintering is controlled to be 2°C / min, and the sintering holding time is 8 hours to obtain a sintered product; (4) The sintered material is crushed to obtain a crushed material, and the median volume distribution particle size D50 of the crushed material is 4.7 μm; 300 g of the crushed material is mixed with 0.5 g of WO3, and the mixture is sintered at 550°C for 8 h in an oxygen atmosphere to obtain a sintered material. The sintered material is sieved and demagnetized to obtain a positive electrode material.
[0081] Example 16 This embodiment provides a positive electrode material, and the preparation process is as follows: (1) Take metal salts of Ni, Co, and Al, prepare a nitrate solution according to the molar ratio of Ni:Co:Al=55:12:33, add K chloride solution to the nitrate solution to prepare a precursor solution, the mass ratio content of K element in the precursor solution is 0.01%, and the total concentration of Ni, Co, Al, and K in the precursor solution is 5 mol / L; (2) The precursor solution is sprayed and then annealed to prepare an oxide precursor, wherein the atomizing air flow rate of the spraying treatment is 200m 3 / h, atomization pressure is 550Kpa, pyrolysis temperature is 500℃, and annealing temperature is 1000℃; (3) The oxide precursor is crushed, and the volume distribution particle size median D50 of the crushed oxide precursor is 3.19 μm; 400 g of the crushed oxide precursor is uniformly mixed with 186.72 g of lithium carbonate and 1.8 g of CeO2, and sintered at 960°C in a compressed air atmosphere, the heating rate of the heating stage of the sintering is controlled to be 2°C / min, and the sintering holding time is 8 hours to obtain a sintered product; (4) The sintered material is crushed to obtain a crushed material, and the median volume distribution particle size D50 of the crushed material is 4.4 μm; 300 g of the crushed material is mixed with 0.5 g of WO3, and the mixture is sintered at 550°C for 8 h in an oxygen atmosphere to obtain a sintered material. The sintered material is sieved and demagnetized to obtain a positive electrode material.
[0082] Embodiment 17 This embodiment provides a positive electrode material, and the preparation process is as follows: (1) Take metal salts of Ni, Co, and Mn, prepare a nitrate solution according to the molar ratio of Ni:Co:Mn=55:12:33, add K chloride solution to the nitrate solution to prepare a precursor solution, the mass ratio content of K element in the precursor solution is 0.01%, and the total concentration of Ni, Co, Mn, and K in the precursor solution is 5 mol / L; (2) The precursor solution is sprayed and then annealed to prepare an oxide precursor, wherein the atomizing air flow rate of the spraying process is 200m 3 / h, atomization pressure is 550Kpa, pyrolysis temperature is 500℃, and annealing temperature is 1000℃; (3) The oxide precursor is crushed, and the median volume distribution particle size D50 of the crushed oxide precursor is 3.20 μm; 400 g of the crushed oxide precursor is uniformly mixed with 186.72 g of lithium carbonate and 1.8 g of CeO2, and sintered at 960°C in a compressed air atmosphere. The heating rate of the sintering heating stage is controlled at 2°C / min, and the sintering holding time is 8 h to obtain a sintered material.
[0083] Embodiment 18 The difference between this embodiment and embodiment 1 is that the metal salts of Ni, Co and Mn are prepared into a nitrate solution according to the molar ratio of Ni:Co:Mn=70:10:20, and the mass ratio content of K element in the precursor solution is 0.04%; the atomizing air flow rate of the spray treatment is 100m 3 / h, the atomization pressure is 700 Kpa, the pyrolysis temperature is 400° C., and the annealing temperature is 1200° C. The other steps are the same as those in Example 1.
[0084] Embodiment 19 The difference between this embodiment and embodiment 1 is that the metal salts of Ni, Co and Mn are prepared into a nitrate solution according to the molar ratio of Ni:Co:Mn=80:10:10; the atomizing air flow rate of the spray treatment is 300m 3 / h, the atomization pressure is 400 Kpa, the pyrolysis temperature is 1000° C., and the annealing temperature is 500° C. The other steps are the same as those in Example 1.
[0085] Embodiment 20 The difference between this embodiment and embodiment 1 is that the metal salts of Ni, Co and Mn are prepared into a nitrate solution in a molar ratio of Ni:Co:Mn=90:5:5; the other steps are the same as those in embodiment 1.
[0086] Comparative Example 1 This comparative example provides a positive electrode material, and the positive electrode material provided in this comparative example is obtained by the following preparation method: (1) synthesizing a hydroxide precursor with a molar ratio of Ni:Co:Mn=55:12:33 by coprecipitation; (2) The oxide precursor was crushed and the crushing D50 was controlled to be 3.24 μm; 400 g of the crushed oxide precursor was uniformly mixed with 186.72 g of lithium carbonate and 1.8 g of CeO2, and the mixture was sintered at 960° C. for 8 h in a compressed air atmosphere to obtain a sintered product.
[0087] The obtained sintered material was crushed to a particle size D50 of 4.2 μm to obtain a crushed material; 300 g of the crushed material was mixed with 0.5 g of WO3, and sintered at 550° C. for 8 h in an oxygen atmosphere to obtain a sintered material, and the sintered material was sieved and demagnetized to obtain a positive electrode material.
[0088] Comparative Example 2 This comparative example provides a positive electrode material, and the positive electrode material provided in this comparative example is obtained by the following preparation method: (1) synthesizing a hydroxide precursor with a molar ratio of Ni:Co:Mn=55:12:33 by coprecipitation; (2) The oxide precursor was crushed and the crushing D50 was controlled to be 3.16 μm; 400 g of the crushed oxide precursor was uniformly mixed with 186.72 g of lithium carbonate, 1.8 g of CeO2, 0.1 g of MgO, and 0.1 g of KOH, and the mixture was sintered at 960° C. for 8 h in a compressed air atmosphere to obtain a sintered product.
[0089] The obtained sintered material was crushed to a particle size D50 of 4.5 μm to obtain a crushed material; 300 g of the crushed material was mixed with 0.5 g of WO3, and sintered at 550°C for 8 h in an oxygen atmosphere to obtain a sintered material, and the sintered material was sieved and demagnetized to obtain a positive electrode material.
[0090] Comparative Example 3 This comparative example provides a positive electrode material, and the positive electrode material provided in this comparative example is obtained by the following preparation method: (1) Pure metal salts of Ni, Co and Mn are prepared into a ternary nitrate solution in a molar ratio of Ni:Co:Mn=55:12:33, and then an oxide precursor is prepared by spray pyrolysis; (2) The oxide precursor was crushed and the crushing D50 was controlled to be 3.48 μm; 400 g of the crushed oxide precursor was uniformly mixed with 186.72 g of lithium carbonate and 1.8 g of CeO2, and the mixture was sintered at 960° C. for 8 h in a compressed air atmosphere to obtain a sintered product.
[0091] The obtained sintered material was crushed to a particle size D50 of 4.1 μm to obtain a crushed material; 300 g of the crushed material was mixed with 0.5 g of WO3, and sintered at 550°C for 8 h in an oxygen atmosphere to obtain a sintered material, and the sintered material was sieved and demagnetized to obtain a positive electrode material.
[0092] Comparative Example 4 1) Take metal salts of Ni, Co and Mn, prepare a nitrate solution according to the molar ratio of Ni:Co:Mn=55:12:33, add K chloride solution to the nitrate solution to prepare a precursor solution, the mass ratio content of K element in the precursor solution is 0.01%, and the total concentration of Ni, Co, Mn and K in the precursor solution is 5 mol / L; (2) The precursor solution is sprayed and then annealed to prepare an oxide precursor, wherein the atomizing air flow rate of the spraying process is 80m 3 / h, atomization pressure is 900Kpa, pyrolysis temperature is 1000℃, annealing temperature is 700℃; (3) The oxide precursor is crushed, and the volume distribution particle size median D50 of the crushed oxide precursor is 3.24 μm; 400 g of the crushed oxide precursor is uniformly mixed with 186.72 g of lithium carbonate and 1.8 g of CeO2, and sintered at 960°C in a compressed air atmosphere, the heating rate of the heating stage of the sintering is controlled to be 2°C / min, and the sintering holding time is 8 hours to obtain a sintered product; (4) The sintered material is crushed to obtain a crushed material, and the median volume distribution particle size D50 of the crushed material is 4.2 μm; 300 g of the crushed material is mixed with 0.5 g of WO3, and the mixture is sintered at 550°C for 8 h in an oxygen atmosphere to obtain a sintered material. The sintered material is sieved and demagnetized to obtain a positive electrode material.
[0093] Test method: The test method for the average concentration X1 of the element M in the center area and the average concentration X2 in the surface area of the positive electrode material grains is as follows: use a Hitachi ion cutting instrument to prepare a section sample, use a Hitachi S4800 scanning electron microscope to select a suitable section field of view, and then use EDS to perform line scanning or point scanning on the grain section within the 5k field of view. For example, the point scanning method can be used to measure the content of the M element at 10 positions (generally at least 5 points) in the center area of the grain section, and the content of the M element is summed and averaged to obtain X1; measure the content of the M element at 10 positions in the surface area of the grain section, and the content of the M element is summed and averaged to obtain X2. Figure 1 As shown, in the grain cross-sectional view, the radius of the grain is L, the area from the center of the grain to the distance L / 2 from the center of the grain is the central area, and the area from the position of L / 2 of the grain to the surface of the grain is the surface area. When the positive electrode material contains two or more elements M, X1 and X2 of each element M are measured separately, and the X2 / X1 value of the corresponding element is calculated accordingly.
[0094] For point scanning and line scanning, combined Figure 6 The instructions are as follows: Scan: In the center area ( Figure 6 Select 5-10 points (inside the red circle shown) for EDS measurement, and take the average value to get the X1 value; in the surface area ( Figure 6 Select 5-10 points (outside the red circle shown) for EDS measurement and take the average value to get the X2 value.
[0095] Line scan: In the central area (i.e. Figure 6 At least three line positions are randomly selected for line scanning (inside the red circle shown), and the average value is taken after measurement to obtain the X1 value; the surface area (i.e. Figure 6 At least three line positions are randomly selected for line scanning (outside the red circle shown), and the average value is taken after measurement to obtain the X2 value. In actual testing, point scanning and line scanning can also be used in combination.
[0096] The test method for the content of each element contained in the positive electrode material is as follows: 0.3g of the positive electrode material sample to be tested is dissolved in aqua regia, cooled and fixed to a volume of 100ml to prepare a mother solution for determination; 1mL of the mother solution for determination is taken, diluted 100 times, and the content of the main elements Li, Ni, Co, Mn, Al and the content of other elements such as element M are tested. The determination is performed using Agilent 5110 ICP-OES detection equipment.
[0097] The test method of microscopic strain size ε is as follows: the test is carried out with the parameters of 1° / min and step size of 0.005° in the range of 10°-70° using the XRD diffractometer of Rigaku Corporation in Japan; the XRD image of the test is then subjected to Rietveld refinement by GASA to obtain information such as the unit cell parameters and peak shape parameters of the sample, and the strain size is calculated according to the Scherrer formula based on the obtained peak shape parameters; the unit cell volume after doping with the M element is compared with the unit cell volume without M element doping. If the unit cell volume becomes smaller after doping with the M element, it means that compressive strain (expressed by a negative number) is introduced into the lattice, otherwise it is tensile strain; the strain size results of the test are shown in Table 3.
[0098] Testing method for specific surface area S: Use American Micrometer tester to test the specific surface area, and test after degassing at 300℃ in vacuum for 1h.
[0099] Testing method for tap density ρ1: Use Dandong Better BT-303 to test the tap density, with a vibration rate of 3000 times / min, a vibration time of 1min, and a vibration amplitude of 3mm±0.1mm.
[0100] Testing method for powder compaction density ρ2: Use compaction density meter to test powder compaction density, 6t pressure for 30s.
[0101] Malvern laser particle size analyzer MS 3000 was used to test the volume particle size of the positive electrode material.
[0102] The calculation formula for the volume particle size distribution width Span value is: Span value = (D90-D10) / D50.
[0103] Hitachi S4800 scanning electron microscope was used to observe the surface morphology and particle size of the samples.
[0104] The electrochemical performance of the positive electrode materials provided in the above embodiments and comparative examples was tested using the following methods.
[0105] First, the positive electrode materials provided in each embodiment and comparative example were mixed with conductive carbon black and binder PVDF (polyvinylidene fluoride) in a mass ratio of 80:10:10, and NMP (N-methylpyrrolidone) was added to prepare a uniform slurry, which was coated on a copper foil, dried in an oven, and rolled at a pressure of 10 Mpa before being cut into circular electrode pieces with a diameter of 14 mm.
[0106] The lithium-ion battery is assembled according to the CR2025 button battery in industry, the diaphragm is Cellgard diaphragm, the electrolyte is 1 mol / L LiPF6 solution with EC / PC / DEC as solvent, and the counter electrode is lithium sheet.
[0107] The entire assembly process of lithium-ion batteries is carried out in a glove box filled with argon, and the oxygen and moisture contents in the glove box are controlled below 0.5 ppm.
[0108] The test conditions for lithium-ion batteries are: temperature is 25℃±1℃.
[0109] The electrochemical cycle performance, capacity, and first efficiency (first efficiency) of lithium-ion batteries were tested. The voltage range of the charge and discharge cycle was 2.8V-4.35V, the current size was 0.1C (20mAh / g), and the cycle test was carried out at 0.5C charge and 1C discharge for 50 weeks. The capacity unit is mAh / g, and the first efficiency unit is %.
[0110] The test results of the average concentration X1 and the average concentration X2 of the element M in the positive electrode materials provided in the above embodiments and comparative examples are shown in Table 1.
[0111]
[0112] The X2 / X1 values of the element M in the positive electrode materials provided in the above embodiments and comparative examples are shown in Table 2. The contents of the element M and the element N2 in the positive electrode materials provided in the above embodiments and comparative examples were also tested, and the test results are shown in Table 2.
[0113]
[0114] The physical and chemical properties test results of the positive electrode materials provided in the above embodiments and comparative examples are shown in Table 3 below.
[0115]
[0116] The electrochemical performance test results of the positive electrode materials provided in the above embodiments and comparative examples are shown in Table 4.
[0117]
[0118] Embodiments 1-20 of the present invention respectively adopt a variety of different elements M, control the different X1 and X2 values of the element M, and different X2 / X1 values in the range of 1.2≤X2 / X1≤20. It can be seen from the above embodiments that the positive electrode material provided by the present invention suppresses the lattice expansion during the charge and discharge process by doping the element M in the positive electrode material and making the concentration of the element M in the surface area of the positive electrode material grains greater than that in the internal area, thereby achieving the purpose of improving the long-term cycle performance. In Comparative Example 1, the precursor was prepared by co-precipitation, and the M element was not used for doping, so its capacity and first effect were significantly weaker. In Comparative Example 2, the precursor prepared by co-precipitation was doped with the K element at the same time, and the value of X2 / X1 was significantly less than 1.2. At the same time, combined with Figure 3It can be seen that the K element is distributed more evenly, the concentration difference between the surface area and the internal area is small, and its capacity and first effect are obviously poor. In Comparative Example 3, the precursor was prepared by spray pyrolysis, but the M element was not doped, and its capacity and first effect were obviously weaker. In Comparative Example 4, the precursor was prepared by spray pyrolysis, and the M element was doped. The X2 / X1 of the obtained positive electrode material was greater than 20, indicating that the M element was enriched in the surface area of the grains, and its cycle stability was weak. The inventor speculated that the compressive stress was too large due to the excessive difference in element concentration between the surface area and the inner area. During the cycle, the grains are more likely to form cracks, thereby reducing the cycle stability.
[0119] Combined with Table 2 Figure 2 It can be seen that there is an obvious concentration difference between the surface area and the internal area of the K element in Example 1, Example 6, and Example 7, and X1 / X2 satisfies the value range of 1.2≤X2 / X1≤20, while in Comparative Example 2, the distribution of the K element is more uniform, and the concentration difference between the surface area and the internal area is smaller. Combined with Table 4, it can be seen that compared with Comparative Example 2, the capacity and first efficiency of the lithium batteries made of the positive electrode materials in Example 1, Example 6, and Example 7 are significantly improved, and the electrochemical cycle performance is also significantly improved. The internal cracks of the positive electrode materials provided in Example 6 and Comparative Example 2 are also compared, and the specific comparison diagram is shown. Figure 4 shown. Figure 4 It can be seen that the cross section of the grain in Comparative Example 2 shows that there are multiple cracks inside the grain, as shown in the white circle mark in the figure, indicating that Example 6 produces fewer microcracks, which is beneficial to improving the gas production performance and is beneficial to long-term circulation.
[0120] It can be seen from Table 3 that the lattice strain ε of the positive electrode material of the present invention is less than 0.1%, the positive electrode material with this strain has fewer internal microcracks and a high long-term cycle capacity retention rate. 2 / g~0.9m 2 / g range, indicating that the surface coating of the positive electrode material is uniform and the discharge capacity is high. The tap density of the positive electrode material ρ1>2.0 g / cm 3 , high tap density, higher pole piece compaction, higher energy density. The compaction density of the positive electrode material ρ2≥2.8 g / cm 3 , the powder compaction density is high, the pole piece compaction is higher, and the energy density is also higher. The volume particle size distribution width Span value of the positive electrode material: 1.5 ≥ Span value ≥ 1.0; the positive electrode material that meets this particle size distribution has higher pole piece compaction, and therefore has a higher energy density.
[0121] The above descriptions are merely embodiments of the present invention and are not intended to limit the patent scope of the present invention. Any equivalent transformations made using the contents of the present invention specification, or directly or indirectly applied in other related technical fields, are included in the patent protection scope of the present invention.
Claims
1. A positive electrode material, characterized in that: The chemical formula of the positive electrode material is: Li a Ni b Co c N1 d M (1-b-c-d-e) N2 e O2, wherein: 0.95≤a≤1.2, 0<b≤1, 0<c≤1, 0<d≤1, 0≤e<1, and b+c+d+e<1; the element M is selected from at least one element of Group IA and Group IA in the periodic table; the element N1 is selected from at least one of Mn and Al, and the element N2 is selected from at least one of Zr, Ti, Al, Co, Mg, W, Ce, and Y; The positive electrode material includes a plurality of crystal grains, and a cross section of the crystal grains includes a central region and a surface region. The cross section of the crystal grains is tested by EDS, and the average concentration of the element M in the central region is measured to be X1, and the average concentration of the element M in the surface region is X2, and X1 and X2 satisfy: 1.2≤X2 / X1≤20.
2. The positive electrode material according to claim 1, characterized in that The content of the element M in the positive electrode material is 10ppm~400ppm; and / or the content of the element N2 in the positive electrode material is 0ppm~5000ppm.
3. The positive electrode material according to claim 1 or 2, characterized in that The positive electrode material includes at least one of the following features (a) to (g): (a) the positive electrode material comprises at least one grain having the same orientation, and the average grain size of the grain is 1µm to 5µm; (b) the lattice strain ε of the positive electrode material is less than 0.1%; (c) The specific surface area S of the positive electrode material is 0.4 m 2 / g~0.9m 2 / g; (d) The tap density of the positive electrode material is ρ1>2.0 g / cm 3 ; (e) The compaction density of the positive electrode material is ρ2 ≥ 2.8 g / cm 3 ; (f) the volume particle size distribution width Span value of the positive electrode material satisfies: 1.5 ≥ Span value ≥ 1.0; (g) The positive electrode material is a single crystal material.
4. The positive electrode material according to claim 1, characterized in that The element M is selected from at least one of Na, K, Mg, Ca, Sr, Ba, Sr, Rb, and Cs.
5. The positive electrode material according to claim 1, characterized in that The crystal grains also include a matrix and a coating, wherein the coating is at least partially coated on the surface of the matrix, and the coating includes at least one of ZrO2, TiO2, Al2O3, CoO, MgO, WO3, CeO2, and Y2O3.
6. The positive electrode material according to claim 1, characterized in that The X1 is 10ppm~400ppm; and / or, the X2 is 10ppm~400ppm.
7. The positive electrode material according to claim 1, characterized in that The value of X2 / X1 is 1.2, 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, 13, 14, 15, 16, 17, 18, 19, 20 or any value between 1.2 and 20.
8. A method for preparing the positive electrode material according to any one of claims 1 to 7, characterized in that: Includes steps: S1: Mixing a mixed salt solution containing Ni, Co and N1 elements with a salt solution containing element M to prepare a precursor solution; wherein the element N1 is selected from at least one of Mn and Al; S2: The precursor solution is subjected to spray pyrolysis treatment to prepare an oxide precursor, wherein the spray pyrolysis treatment includes spray treatment and annealing treatment, and the atomizing air flow rate of the spray treatment is 100m 3 / h~300m 3 / h, the atomization pressure is 400Kpa~700Kpa, the pyrolysis temperature is 400℃~1000℃, and the annealing temperature is 500℃~1200℃; S3: Mix the oxide precursor with a lithium source and a metal oxide containing element N2 and sinter them to obtain a positive electrode material; the element N2 is selected from at least one of Zr, Ti, Al, Co, Mg, W, Ce, and Y.
9. The preparation method according to claim 8, characterized in that: The preparation method satisfies at least one of the following conditions: (1) The total concentration of Ni, Co, N1, and M in the precursor solution is 2 mol / L to 8 mol / L; (2) The heating rate of the heating stage of the sintering is controlled to be 0.5°C / min to 3°C / min, and the sintering holding time is 8h to 16h; (3) The oxide precursor is mixed with a lithium source and a metal oxide containing elemental N2 in a mass ratio of 1:(0.4-0.8):(0.003-0.006).
10. A lithium ion battery, characterized in that: The lithium-ion battery comprises the positive electrode material according to any one of claims 1 to 7 or the positive electrode material obtained by the preparation method according to any one of claims 8 to 9.
Citation Information
Patent Citations
Lithium ion battery cathode material precursor, lithium ion battery cathode material, preparations methods of lithium ion battery cathode material precursor and lithium ion battery cathode material, and lithium ion battery
CN110422889A
Positive electrode active material for lithium secondary battery and manufacturing method therefor
CN110431695A
Ternary positive electrode material, preparation method thereof and lithium ion battery
CN112803010A
Single crystal type multi-element positive electrode material, preparation method thereof and lithium ion battery
CN116053435A
Gradient doping modified positive electrode material and preparation method and application thereof
CN118754216A
Cited By
Positive electrode material, positive electrode sheet and lithium-ion battery
WO2026138719A1
Positive electrode active material for lithium ion secondary battery, and lithium ion secondary battery
WO2026197296A1